ASM Handbook. Volume 13C, (ASM International, 2006)
Volume 13C examines the process of corrosion and its effects in various industries, environments, and applications. It provides detailed explanations of charge transfer reactions that occur in fresh water, marine, underground, and military environments and its economic and human impact on fossil fuel and nuclear power, land and air transportation, mining and metal processing, pulp and paper production, medical, chemical, and other industries -- publisher.